QoS Measurement of RPL using Cooja Simulator and Wireshark Network Analyser - Kalavathi, P; Charles, A.S. Joseph (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Things (IoT), with its ability to collect data using sensors and store the voluminous data over the cloud has become the de facto standard in building up smart homes and smart cities. The routing protocols are used in the network layer and they play the pivotal role. They perform the intelligent task of forwarding and routing. If the routing is not done properly then there will be a heavy loss and retransmission of the packets, that would cost more power, memory, bandwidth and procession capacity. Therefore, the routing protocols used in the regular networks cannot be used efficiently in IoT. IPv6 routing protocol for Low power and lossy networks (RPL) has become the favourite routing protocol of Internet of Things. There are several metrics used in the RPL to determine the path cost and to help to connect the nodes with each other. The performance quality of RPL can be analysed and measured from the factor that how best it works utilizing the resources like energy, memory, bandwidth etc. The quality of services parameters like packet delivery ratio, network convergence time, remaining energy, latency and control traffic overhead are analysed to measure the performance of RPL. The Cooja simulator running over the Contiki Sensor OS is chosen as an ideal platform due to its special feature of supporting the cross-level simulation. The open source network analyser Wireshark used in Contiki OS also helps in the process of performing the protocol analysis.